\((3x-6)(x-2)^{-1}=3\)

\(\frac{3x-6}{x-2}=3\)

\(3x-6=3(x-2)\)

\(3x-6=3x-6\)

Since this is true for all values of x with the exception of \(x = 2^{1}\), so the answer choice is G.

Note:(1) if \(x = 2\), we are dividing by 0, bit we can't divide by 0, so can't be 2.

\(\frac{3x-6}{x-2}=3\)

\(3x-6=3(x-2)\)

\(3x-6=3x-6\)

Since this is true for all values of x with the exception of \(x = 2^{1}\), so the answer choice is G.

Note:(1) if \(x = 2\), we are dividing by 0, bit we can't divide by 0, so can't be 2.